First record of Plethus Hagen (Trichoptera, Hydroptilidae) from Japan, with description of a species - Ito, Tomiko; Saito, Rie (Zootaxa, 2016)
The tropical and subtropical caddisfly genus Plethus Hagen (Hydroptilidae) is recorded from Japan for the first time. The species, Plethus ukalegon Malicky and Chantaramongkol 2007, originally described from Taiwan, is redescribed based on material from Iriomote-jima and Ishigaki-jima, southern Ryukyu Islands, the southernmost region of Japan. Female and immature stages are newly described and compared with Indonesian congeners. The early instar larva was associated with the adult through mitochondrial DNA sequence comparisons, and is described in the genus Plethus for the first time. Larvae live in fast-flowing waters such as hygropetric zones, rapid streams, and waterfalls. Final instar larvae make flattened cases of silk that they attach tightly on smooth rock surfaces.